Pengaruh Proses Produksi Garmen dan Pengendalian Kualitas terhadap Efektivitas Produksi di Perusahaan Garmen Semarang - Nabila Rahmanisa; Karjono; Evyana Diah Kusumawati (Politeknik bumi Akpelni, 2025)
This study aimed to examine the extent to which production processes and quality control contribute to the improvement of garment production effectiveness at a garment company in Semarang. The research method used is a quantitative method with a correlational approach. The sampling technique used is purposive sampling. In this case, the sample is 66 employees from the physical and final quality control (QC) departments. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination test 1 (R2), simultaneous test (F), and partial test (t). The results of hypothesis testing in this study indicate that the production process has a positive and significant effect on production effectiveness, where the significance value of t < 0.001 is < 0.05 and the calculated t of 5.282 > the table t of 1.67722. Furthermore, quality control also has a positive and significant effect on production effectiveness, where the significance value of t is 0.002, which is < 0.05 and the calculated t of 3.297 > the table t of 1.67722. Simultaneously, the production process and quality control have a positive and significant effect on production effectiveness, where the significance value of F < 0.001 is < 0.05 and the calculated F value of 344.555 > the table F of 4.043.